Medical Management of Vasovagal Syncope: A Network Meta Analysis - Loomba, Rohit S.; Nijhawan, Karan; Aggarwal, Saurabh; Arora, Rohit R. (Cardiology and Cardiovascular Medicine, 2017)
Introduction: Multiple pharmacologic therapies have been studied to prevent recurrence in patients with vasovagal syncope. Multiple head to head comparisons have been done with varying results. We aimed to perform a network meta-analysis to assess the efficacy of pharmacologic therapies in preventing recurrent syncope in patients with vasovagal syncope. Methods: A systematic review of the literature was performed to identify randomized controlled trials describing recurrence of vasovagal syncope after initiation of pharmacologic treatment in patients with syncope who had a baseline positive tilt table test. A Bayesian network meta-analysis was conducted utilizing the geMTC package available for R: A Language and Environment for Statistical Computing. Results: None of the included pharmacological therapies were found to significantly reduce the recurrence of vasovagal syncope when compared to placebo. When compared to one another atenolol did offer significant reduction in syncopal episodes when compared to cafedrine. Dihydroergotamine ranked the highest while cafedrine ranked the lowest. Conclusions: Pharmacologic therapies do not offer significant reduction in recurrence of vasovagal syncope. First line therapy for these patients should include lifestyle changes such as increased fluid intake, and when appropriate, increased salt intake.